2010
DOI: 10.1002/adma.201000766
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Spatial Atomic‐Layer Deposition of Aluminum Oxide Layers for Solar Cell Passivation

Abstract: Al2O3 thin films deposited at rates as high as 1.2 nm s−1 using spatially separated atomic layer deposition show excellent solar cell surface passivation properties, i.e., recombination velocities of <2 cm s−1. This disruptive ALD concept opens the way for cost‐effective manufacturing with high industrial throughput numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
236
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 309 publications
(239 citation statements)
references
References 12 publications
(19 reference statements)
2
236
0
Order By: Relevance
“…2. The separate reaction zone inlets are incorporated in a round reactor head, surrounded and separated by gas-bearing planes [ Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The separate reaction zone inlets are incorporated in a round reactor head, surrounded and separated by gas-bearing planes [ Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 Whereas for conventional ALD the precursors are dosed one by one, separated in time by a purge or pump step, in spatial ALD the precursors are dosed simultaneously and continuously, but separated in space. The main advantages of spatial ALD are the high deposition rate that can be achieved (nm/s for alumina, 2 as compared to $nm/min for conventional ALD), the possibility to conduct atmospheric pressure deposition, and the absence of parasitic deposition in the reaction chamber. One of the first industrial applications exploited today for spatial ALD is surface passivation of crystalline silicon solar cells, [3][4][5] and new applications, such as encapsulation, diffusion barriers, and roll-to-roll processing, are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, considerable interest in Al 2 O 3 surface passivation films for silicon photovoltaics has developed over the last few years, 21,22 which also spurred the development of ALD processes for high-volume manufacturing. 22,23 For the synthesis of Er 2 O 3 by ALD, on the other hand, only a few reports exist. Päiväsaari et al reported an ALD process for Er 2 O 3 , using Er(thd) 3 and Er(CpMe) 3 as precursors, in combination with O 3 and H 2 O as oxidants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Spatial-ALD combines the advantages of conventional ALD (e.g., superior control of film composition, growth of uniform, pinhole free, and highly conformal thin-films on large area and flexible substrates) with high deposition rates (up to $nm/s). 11 For this reason, atmospheric pressure spatial-ALD is emerging as an industrially scalable technique for the deposition of thin film electrodes (e.g., ZnO) and encapsulation (e.g., by Al 2 O 3 thin-films) of solar and electronic devices. 10,12 In this paper, we report on the stability of the electrical, optical and structural properties of spatial-ALD intrinsic (i-ZnO) and In-doped ZnO (In:ZnO) films, exposed to a high humidity and high temperature environment [85% relative humidity (RH), 85 C].…”
Section: Introductionmentioning
confidence: 99%